REVERSING THE LENS, WACANA PERLAWANAN SEJARAH 1965 DALAM FILM THE ACT OF KILLING - Witriani, Witriani (Adabiyyāt: Jurnal Bahasa dan Sastra, 2018)
As a study, documentary film is often used as a reference because of its historical, social, cultural and political representation which signifies the facts in society. It is no wonder that the production as well as the analysis of the film genre and its development around the world have created such debate, including in the academic realm. The film The Act of Killing is one of them. Directed by an American filmmaker, Joshua Oppenheimer, the film tries to reveal the other facts of Indonesian history which have been covered and never imagined before, especially, the implications of Indonesian Communist Party (PKI) massacre in 1965. Taking the testimony of the actors, the film is quite controversial because it tells and descibes kind of sadism and human rights violations on PKI elements and other ethnicity. Thus it changes the world opinion about the Indonesian history in 1965. However, as a construction, film is a film. Sometimes, there is always a bias. What depicted in a film is a result of the cineast interpretation of historical events that may be different from other point of view. For instance, a contradictory between humanity and ideology has created a discourse among the viewers. While the director focus on a violation of human rights and set everything based on this perspectives, the actors or the perpetrators feel that what they did was a form of struggle to defense the country.